Participation: housing and urban viability - Miles, Malcolm (Journal of Architecture and Urbanism, 2013)
In the global North, housing tends to be seen as a sub-sector of the construction industry. In the global South, in contrast, it might be considered more as a verb – housing as the activity of meeting basic needs for shelter. As such, this process is frequently undertaken by users themselves, in the informal settlements which surround most cities. While these settlements were once regarded as a threat to the urban order (or urbanization), today there is increasing recognition that self-build and self-managed housing meets the needs of urban development in ways which are usually more sustainable as well as lower-cost than standard housing schemes (whether in the public or the private sector). This paper begins from the question as to how far the lessons of informal settlements in the South can be applied in the North. It looks at the status of informal settlements in the new South Africa, and at two schemes in the UK: the Coin Street development in London, managed by tenants; and Ashley Vale self-build housing in Bristol, in southwest England. These are not seen as exemplary but simply two cases which can be compared and contrasted in the terrain of new approaches to building cities for the future.